Study of Protein, Cholesterol and Glycogen in Acetes Spp from West Coast of Maharashtra, India - Sonal Salvi; Bhavita Chavan (Journal of Indian Fisheries Association, 2020)
Biochemical composition of the sergestid planktonic shrimp, Acetes spp was studied during January 2016 – June 2016, from selected stations along the west coast of Maharashtra. Acetes spp, a Sergestid shrimp is estimated to contribute about 20% of the marine prawn landings along the west coast of Maharashtra. Only small portion of the catch is consumed fresh and the rest is mostly sun-dried. Much of the catch is often wasted and less attention given to the nutritional value of Acetes shrimp, which contains protein, water and also a small amount of fat. Hence, the present study was undertaken to estimate total protein, cholesterol and glycogen from Acetes spp samples collected from three major harbours Mumbai, Uran and Ratnagiri along Maharashtra coast. The results show Acetes spp. has high nutritional values as of the other shrimps, also easily available at market at less cost as compared to other high market value shrimps and thus can be a good substitute for other shrimps.